The Influence of Organizational Culture, Supervision, and Job Satisfaction on Employee Performance at PT. DEF - Mas’ud, Anis Anshari; Afrianti, Rini; Yunia, Noorma; Murni, Yanti; Aini, Rohana Nur (Universitas Sulawesi Barat, 2025)
This study aims to examine the influence of organizational culture, supervision, and job satisfaction on employee performance at PT. DEF Balikpapan. Although similar studies have been conducted previously, the novelty of this research lies in evaluating organizational behavior factors within the context of a heavy-equipment company that is undergoing digital transformation and tighter performance monitoring. Using a quantitative approach and saturated sampling of 27 employees, data were analyzed using multiple linear regression. Results indicate that organizational culture has a negative but insignificant effect on performance, supervision has no positive influence, while job satisfaction significantly improves performance. Simultaneously, the three variables significantly affect employee performance. These findings contribute to literature by highlighting the inconsistency of cultural and supervisory effects in companies with evolving digital work systems and restricted autonomy